2016
DOI: 10.18052/www.scipress.com/ilns.54.42
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Thermodynamic Study of Phenol Removal from Water Using Activated Carbon Synthesizes from Avocado Kernel Seed

Abstract: ABSTRACT. This study was aimed for removal of phenol from water using activated carbon synthesize from avocado kernel seeds by adsorption onto it. For adsorption process cleaned and washed avocado kernel seeds (Persea americana) were dried at 100°C in an oven overnight and carbonization was carried out by increasing the furnace temperature at a rate of 5 °C/min to a final temperature of 800 °C for 160 minutes. Then, the activated carbon was powdered and sieved, washed with distilled water until the solution pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…In similar conditions, the removal efficiency will get reduced to 60.8% if the concentration is increased to 100 mgL -1 . This result is consistent with the results obtained by Dejene et al in 2016 [28] and Ghoreyshi et al in 2014 [29]. Moreover, Jafarimansorian et al in 2013 reported in their study on the removal of methylene blue by means of walnut shell ashes that the efficiency will be reduced if the initial concentration of methylene blue is increased.…”
Section: Results Of the Effect Of Initial Methylene Blue Concentrationssupporting
confidence: 91%
See 2 more Smart Citations
“…In similar conditions, the removal efficiency will get reduced to 60.8% if the concentration is increased to 100 mgL -1 . This result is consistent with the results obtained by Dejene et al in 2016 [28] and Ghoreyshi et al in 2014 [29]. Moreover, Jafarimansorian et al in 2013 reported in their study on the removal of methylene blue by means of walnut shell ashes that the efficiency will be reduced if the initial concentration of methylene blue is increased.…”
Section: Results Of the Effect Of Initial Methylene Blue Concentrationssupporting
confidence: 91%
“…One of the important parameters in the adsorption process is the amount of the pH value of the aqueous solution [28,29]. In this study, the effect of the initial pH of the solution (range of 5-9) on the removal efficiency of methylene blue by the rice husk silica (adsorbent dose of 1 gL -1 with 50 mgL -1 methylene blue and a contact time of 60 minutes) was investigated.…”
Section: Results Of the Ph Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive value of ΔH° indicates the endothermic nature of the process of adsorption and suggests that the transfer of the ions of phenol of the aqueous phase to the solid phase requires energy. As, we notice as in the presence of formic acid ΔH° ˃ 40 kJ/mol representing a high energy that would indicate that the reaction of adsorption of phenol would be a chemical adsorption on the other hand in absence of formic acid ΔH°˂ 40 kJ/mol, the reaction of adsorption of phenol would be a physical adsorption, the similar results were reported recently (Kassahun and al., 2016).…”
Section: Study Of Thermodynamic Of Adsorptionsupporting
confidence: 89%
“…The authors showed that the positive correlation between pyrolysis temperature and hydrophobic interactions, thus hydrophobicity, is a driving force in the sorption of MC-LR. Teixidó et al [118] described sorption removal of hydrophilic sulfamethazine by biochar with electron donor-acceptor interaction between protonated aniline ring and on π-electrons rich carbon surface as the predominant driving force. However, this kind of interaction is not a major force during MCs interactions with biochar-based sorbents.…”
Section: Biochar For Microcystin Sorption Separationmentioning
confidence: 99%